Optimization of Biofertilizer Microbial Consortium from Several East Java Lakes for Lettuce Growth using NFT Hydroponic System - Wuryanti Syalwa Dida; Prabanigtyas Sitoresmi; Katikasari Nur’aini (BIO Web of Conferences, 2025)
It is important to note that land conversion poses a significant challenge to lettuce cultivation. This has prompted the need to enhance production through hydroponics. Hydroponics relies on water-distributed nutrients, and it has been suggested that organic nutrients in the form of microbial consortiums from various East Java lakes, such as Bacillus paramycoides and Delftia sp., could serve as an alternative to optimize growth and minimize the application of an AB mix in facilitating lettuce plant growth within the NFT hydroponic system. The treatment levels provided are P0: 100% purified water; P1: 75% biofertilizer + 25% AB mix; P2: 50% biofertilizer + 50% AB mix; P3: 25% biofertilizer + 75% AB mix; P4: 100% AB mix; and P5: 100% biofertilizer. The results show that the combination treatment of 75% biofertilizer + 25% AB mix, classifying it as the best combination to reduce the use of inorganic fertilizer.